Conversion of the Belief System of the Riau Islands Sea Nomads (Suku Laut) 1999–2026 - Sinta Soptapia; Novita Mandasari Hutagaol; Fitri Yanti; Tri Tarwiyani; Arnesih Arnesih (Journal of Philology and Historical Review, 2026)
This study examines the belief system conversion among the Suku Laut (Sea Nomads) community in the Riau Islands from traditional beliefs to religion. It focuses on the traditional belief systems of the Suku Laut prior to the introduction of religion, the process of religious transformation, and its impact on the community's cultural identity. Using a historical method with an oral history approach, primary data were obtained through in-depth interviews with members of the Suku Laut community in Lingga, Batam, and Pongok Island, while secondary data were gathered from relevant books, scientific articles, and previous studies. The findings reveal that prior to adopting a religion, the Suku Laut community had developed a local religiosity rooted in a spiritual connection with the sea, taboos, seasonal knowledge, and beliefs in natural signs. The shift toward religion occurred gradually, influenced by changes in settlement patterns, social interactions, education, and state intervention through coastal resettlement programs. Although the community has embraced religion, several elements of their traditional beliefs persist in daily life. This study demonstrates that the conversion of the belief system among the Suku Laut did not occur as a total replacement, but rather through cultural negotiation and the reconstruction of religious identity within the maritime indigenous community of the Riau Islands.